2021
DOI: 10.1016/j.acra.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Pediatric COVID-19 on Chest Radiography and Chest CT: A Retrospective, Single-Center Study

Abstract: Rationale and Objectives: This study aims to reveal the imaging features of Coronavirus Disease 2019 (COVID-19) in children. Materials and Methods: Sixty-nine chest radiographs and 37 chest CT examinations of 74 children (36 male; median (interquartile range) age:11 (6.25À15) years, 38 female; median (interquartile range) age: 12 (5.75À16) years) with positive real-time reverse transcription-polymerase chain reaction results between March 10 and May 31, 2020, were evaluated in this retrospective study. Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
(52 reference statements)
0
42
2
Order By: Relevance
“…A study by Bayramoglu, et al demonstrated that nearly half of children with COVID-19 had ground glass opacities either with or without accompanying consolidation. Further, they identified the feeding vessel sign, halo sign, pleural thickening, interlobular interstitial thickening, and lymphadenopathy as other frequent chest imaging signs in children with COVID-19 ( 107 ). A meta-analysis evaluating imaging findings of COVID-19 in 850 children demonstrated a 61.5% rate of ground glass opacities or consolidation.…”
Section: Covid-19 In the Pediatric Populationmentioning
confidence: 99%
“…A study by Bayramoglu, et al demonstrated that nearly half of children with COVID-19 had ground glass opacities either with or without accompanying consolidation. Further, they identified the feeding vessel sign, halo sign, pleural thickening, interlobular interstitial thickening, and lymphadenopathy as other frequent chest imaging signs in children with COVID-19 ( 107 ). A meta-analysis evaluating imaging findings of COVID-19 in 850 children demonstrated a 61.5% rate of ground glass opacities or consolidation.…”
Section: Covid-19 In the Pediatric Populationmentioning
confidence: 99%
“…Although the concept that radiological manifestations of COVID-19 vary among different age group, information about sensitivity, specificity and characteristic findings of chest X-ray in the pediatric population are limited and conflicting[ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peribronchial thickening is however aspecific and can be seen in other variant of viral pneumonia in children, while hyperinflation, which is another recognized hallmark, was not reported. Reason for chest X-ray low sensitivity is the higher prevalence of lower density, smaller size and basal opacities, obscured by the diaphragm and hepatic dome[ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the case report of 2 cases by of elderly female and male 1/6/10R and 2R/4R/4L respectively on the both their first CT chest and their repeat CT chest after 6 d[ 19 ]. In a retrospective review of CT chest in pediatric patients with COVID-19, mediastinal lymphadenopathy was found in 0%-8.1% of the cases[ 20 , 21 ]. Mediastinal lymphadenopathy was not reported in pregnancy patients with COVID-19[ 22 ].…”
Section: Mediastinal Lymphadenopathy In Coronavirus Disease 2019 Infectionmentioning
confidence: 99%